Influence of traditions of law on law-making in Kievan Rus' - Shevchenko, Anatolii Yevheniiovych; Kudin, Serhii Volodymyrovych; Kapichon, Olha Hryhorivna (Scientific Publishing Center “Sci-conf.com.ua”, 2020)
National law-making is inconceivable without taking into account the significance of the existence of a legal system based on ideas that reflect national legal awareness. That is why close attention should be paid to the formation of the national legal system at key stages in the development of Ukrainian society. One of these stages is the period of Kievan Rus'.

Національне законодавство немислиме без урахування значення існування правової системи, заснованої на ідеях, що відображають національну правову обізнаність. Саме тому пильну увагу слід приділяти формуванню національної правової системи на ключових етапах розвитку українського суспільства. Одним із таких етапів є період Київської Русі.
Keywords: law; Eastern Europe; Ukraine; legal traditions; Kievan Rus; law; право; Східна Європа; Україна; правові традиції; Київська Русь; закон